ANALYSIS OF INTERCEPTOR POSITION VARIATIONS TO OPTIMIZE THE EFFECT OF RESISTANCE ON A CATAMARAN - Ahmad Fadil Rahman (Fakultas Teknik UPN Veteran Jakarta, 2026)
Catamarans are multihull vessels that offer superior stability and lower resistance potential compared to monohull ships. For high-speed vessels, one method commonly used to reduce hydrodynamic resistance is the installation of an interceptor at the stern. This study aims to analyze the effect of interceptor position variations on the total resistance of a catamaran using the Computational Fluid Dynamics (CFD) method. The interceptor configurations investigated include no interceptor, full interceptor, partial near keel, and partial near side. Simulations were conducted using ANSYS Fluent with variations of Froude numbers 0,6; 0,8; 1,0; 1,2. The results indicate that total resistance increases with increasing Froude number. Among the configurations studied, The use of a full interceptor provides the lowest total resistance value with a resistance value of 13.9 N compared to other variations, although the difference is relatively small with a decrease in the resistance value of around 1,03%.. Therefore, it can be concluded that the full interceptor is the most optimal configuration for reducing the total resistance of a catamaran under the conditions examined in this study